Johor Bahru district identity through lawsonia anermis for public transport personnel uniform / Nur Suria Farhana Mohd Tajul Arifin and Rainal Hidayat Wardi - Mohd Tajul Arifin, Nur Suria Farhana; Wardi, Rainal Hidayat (Universiti Teknologi MARA, 2021)
The uniforms of public transport that public employees wear currently are a moving visual identification persuading a corporation's appearance and a key factor in deciding public transportation for consumers who receive services from. Based on the increasing heavy usage of public transport in Malaysia, it views this trend as a great opportunity as a platform to expand and emphasizes red henna flowers or Lawsonia Anermis design through public transport personnel uniform in Johor Bahru district. Some of society does not know that Lawsonia Anermis's motif is the symbol of the Johor Bahru district. Moreover, this motif has not yet been introduced or expanded at any personnel uniform. Besides, the problem statement of this research that concern about there is not many groups using and do exploration about Lawsonia Anermis's motif as a design on any personnel uniform for public transport workers. Therefore, proper public transport personnel uniforms have to be developed by reflecting the image and identity of Johor Bahru through its official flower of Lawsonia Anermis. There are three goals to accomplish this research goal which is to discover a significant of Lawsonia Anermis plants that are associated with Johor Bahru official flower. Next, to determine the potential of Lawsonia Anermis plants into design elements. Lastly, to identify proper design criteria for public transport personnel uniforms based on Lawsonia Anermis conception. In this research, the true quantitative method was applied. The primary data includes questionnaires, photo records and sampling. The secondary data includes the internet, articles and books. Next, the data analysis will be distributed to 100 respondents of public transport workers in the Johor Bahru district. Although the sample study is limited, the outcome of this paper can be widely used as a reference and important guidelines for the design of personnel uniforms to create local identity integrity and thus able to establish the identity of a local and foreign.